Ancient Rome at the cinema : story and spectacle in Hollywood and Rome - Theodorakopoulos, Elena (Exeter : Bristol Phoenix, 2010)
- Introduction##- Narrative and spectacle, realism and illusion, and the historical film##- Ben-Hur : 'tale of the Christ' or tale of Rome?##- Spartacus and the politics of story-telling##- The fall of the Roman Empire : the filmmaker as historian##- Gladiator : making it new?##- Fellini Satyricon : 'farewell to antiquity' or 'daily life in ancient Rome'?##- Titus : Rome and the penny arcade##- Conclusion.
Includes bibliographical references and index.
boek